Geriatric nursing home falls: A single institution cross-sectional study. (March 2016) - Botwinick, Isadora; Johnson, Joshua H.; Safadjou, Saman; Cohen-Levy, Wayne; Reddy, Srinivas H.; McNelis, John; Teperman, Sheldon H.; Stone, Melvin E.
Highlights: Nursing home patients have more comorbid conditions and more debilitated on admission. Nursing home patients have increased rates of in-hospital complications. In-hospital mortality is not different between community and nursing home patients. Abstract: Background: Falls are the leading cause of fatal injury in geriatric patients. Nursing home falls occur at twice the rate of community falls, yet few studies have compared these groups. We hypothesized that nursing home residents admitted for fall would be sicker than their community counterparts on presentation and have worse outcomes. Methods: Records of 1708 patients, age 65 years and older with a documented nursing home status, admitted to our center between 2008 and 2012 were reviewed. Clinical data including injury severity score (ISS), admission Glasgow coma scale (GCS), in-hospital complications, length of stay (LOS), and in-hospital mortality were collected. Continuous data were analyzed using Mann–Whitney tests and categorical data using Fisher exact tests. Variables in the univariate tests were analyzed in a multivariate logistic regression. Results: Nursing home patients were older than community patients, presented with lower GCS, lower hemoglobin, higher international normalized ratio (INR) and a higher percentage of patients with body mass index (BMI) < 18.5. LOS for nursing home patients was longer, and they suffered higher rates of in-hospital complications. ISS, rates of traumatic brain injury, operative intervention and mortality were not significantly different. In a multivariate logistic regression, ISS, GCS and age, but not nursing home status, were significant predictors of in-hospital mortality. Conclusions: In comparison to their community counterparts, nursing home patients presenting after fall are more debilitated and have increased morbidity as evidenced by more in-house complications and increased LOS. However, nursing home residency was not a significant predictor of mortality.